Students’ Perception on the Use of Android-Based Application e-Ujian for the Final Examination: A Case Study at SMP Atthayyibah Kerinci - Arie Setiadi; Tedy Kurniadi (Mathematics Education Study Program, 2025)
In the context of the rapid advancement of technology, the implementation of digital platforms in education has become essential. This study focuses on students’ perceptions at SMP Attayyibah Kerinci regarding the use of an Android-based application e-Ujian for conducting final examinations. Employing a quantitative descriptive survey design, data are collected through structured questionnaires distributed to 226 Grade IX students. The study examines two primary variables: Perceived Ease of Use (PEOU) and Perceived Usefulness (PU). The findings indicate overwhelmingly positive perceptions, with 91.7% of students agreeing that the application was easy to use, and 83.6% perceiving it as beneficial for exam efficiency and accuracy. However, areas such as answer modification and error reduction require refinement. The findings suggest that the e-Ujian application is an effective tool for modernizing assessments, offering significant advantages over traditional methods, such as reduced costs, enhanced security, and improved efficiency. Recommendations include user training, interface refinement, and future research into its broader applicability. The study concludes that the Android-based e-Ujian is a promising innovation for enhancing educational assessment processes.